Distribution and activity of Drosophila suzukii in cultivated raspberry and surrounding vegetation - Klick, J.; Yang, W. Q.; Walton, V. M.; Dalton, D. T.; Hagler, J. R.; Dreves, A. J.; Lee, J. C.; Bruck, D. J. (Journal of applied entomology (1986), 2016)
Spotted wing drosophila, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), may utilize wild ‘Himalaya’ blackberry (HB) Rubus armeniacus Focke or other non‐crop plants as refugia and possibly exploit adjacent field margins before colonizing cultivated fruiting crops. Studies were conducted to determine the role of field margins containing HB and their effect on D. suzukii activity, density and distribution in an adjacent commercial red raspberry crop. One‐ha plots adjacent to field margins containing HB or known non‐host (NH) grass crops were established in 2011 and 2012 and replicated three times. Each plot contained two transects with monitoring traps for D. suzukii in the field margin (0 m) and spaced approximately 10 (crop boundary), 40, 70 and 100 m into the adjacent crop (n = 10 traps/plot). Field margin vegetation was treated with a 10% chicken egg white mark solution weekly from pre‐harvest until the end of harvest using a cannon sprayer. Adult D. suzukii were collected from traps weekly and analysed for the presence of the egg white mark using an egg white‐specific enzyme‐linked immunosorbent assay (ELISA). During both years, marked flies and total flies were captured in higher numbers in HB field margins, whereas virtually no flies were captured in field margins containing no known alternative host. Similarly, more flies were captured in the crop near HB than near NH. Spatial Analysis by Distance IndicEs (SADIE) and mean D. suzukii trap captures additionally displayed significantly higher fly densities in the raspberry field near HB than near NH. These results suggest that HB may contribute to elevated D. suzukii populations and pest pressure in comparison with field margins containing no known alternate host vegetation for D. suzukii. Having closely adjacent non‐crop alternate host landscapes may result in increased D. suzukii pest pressure.